Postawy i zachowania prokreacyjne matek pracujących w okresie rozwoju rodziny - Szuman, Alicja (Wydział Prawa i Administracji UAM, 1989)
The purpose of the article is to determine the influence of professional activity of mothers on procreation attitudes and behaviours of these women in the family formation period. The study is based on the questionnaire conducted among 1459 mothers. The analysis showed that professional activity of mothers influences the procreation activity, decreasing the number of children and prolonging the periods between consecutive births. Most working mothers in reproductive age resign from having more children, especially mothers having already 2 or 3 children. The percentage of one-child mothers not wanting to have more children is also high, a phenomenon which evokes serious concerns from a demographic point of view. Motivation for resigning from having more children is diversified. The most frequent reasons are: the increase in costs of bringing up children poor condition of mother's health and inadequate housing conditions.
Procreation attitudes and behaviours of working mothers in the family formation period